Predictors of the efficacy of intraoperative radiotherapy in organ-preserving treatment of early breast cancer - N. A. Alaichiev; E. A. Usynin; A. V. Doroshenko; I. V. Kondakova; E. Yu. Garbukov; E. E. Sereda; Zh. A. Startseva; M. A. Vostrikova; A. G. Ivanova (Сибирский онкологический журнал, 2023)
Background. Despite the improvement in combined modality treatment of early breast cancer (BC), the rate of locoregional recurrence remains in the range of 7-15 %. Therefore, the search for prognostic factors for BC is of great significance. The aim of the study was to estimate the relationship between clinical and morphological parameters and 10-year recurrence-free survival rate in BC patients after combined modality treatment including intraoperative radiotherapy (IOLT). Material and Methods. The study enrolled 383 patients with morphologically verified T1-3N0-1M0 stage breast cancer. The median age of the patients was 53 years (range: 28 to 80 years). All patients underwent breast-conserving surgery with IOLT delivered to the tumor bed at a single dose of 10 Gy (24.8 Gy according to the iso-effect). External beam radiation therapy (EBRT) to the conserved breast was given in the postoperative period. Results. Within the 10-year follow-up, 20 (5.2 %) locoregional recurrences occurred, of which 7 (35 %) developed with a primary tumor size of ≤ 2 cm (T1), and most recurrences - 13 (65 %) were detected with the primary tumor size corresponding to T2-3. In patients with luminal A subtype of BC and in patients with triple negative BC, the recurrence rates were 5 % and 45 %, respectively. The 10-year survival rate of patients after combined modality treatment with IOLT was 94.8 %. Conclusion. The results obtained indicate the relationship between the recurrence rate and clinical/ morphological parameters of the tumor, such as tumor size and molecular subtype. These parameters should be taken into account when planning treatment in patients with early BC.